2017
DOI: 10.1182/bloodadvances.2017006130
|View full text |Cite
|
Sign up to set email alerts
|

Management of venous thromboembolism during thrombocytopenia after autologous hematopoietic cell transplantation

Abstract: Key Points• Anticoagulation continuation vs cessation during thrombocytopenia did not affect recurrent thrombosis or bleeding after autologous HCT.• Among anticoagulated patients undergoing autologous HCT, higher platelet counts were not associated with a lower risk of bleeding. Management of venous thromboembolism (VTE) remains challenging in patients withhematologic malignancy who undergo hematopoietic cell transplantation (HCT) due to prolonged thrombocytopenia. This study aims to (1) determine the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 22 publications
1
26
1
Order By: Relevance
“…showed that there was no threshold at which higher platelet counts could predict a decreased risk of bleeding among these patients [32].…”
Section: Discussionmentioning
confidence: 97%
“…showed that there was no threshold at which higher platelet counts could predict a decreased risk of bleeding among these patients [32].…”
Section: Discussionmentioning
confidence: 97%
“…Potential risks of increased transfusion targets include depletion of platelet supplies, increased costs, refractoriness to platelet transfusion and adverse effects, such as arterial and venous thrombosis, volume overload and non-haemolytic febrile transfusion reactions. [30][31][32][33] Furthermore, increased transfusion targets are often not met, resulting in high rates of anticoagulation discontinuation. 30,32 Importantly, there are no data on the efficacy of this transfusion strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, balancing the thrombotic and bleeding risk in thrombocytopenic risk remains a clinical challenge. Unfortunately, prospective data are scarce, meaning that management is currently informed mainly by expert opinion [ 112 ] and retrospective studies on VTE and ischemic heart disease [ 102 , 106 , 113 , 114 , 115 , 116 ], since clinical trials of anticoagulants in cancer-associated VTE exclude patients with thrombocytopenia (<50–100 × 10 9 /L) [ 117 , 118 , 119 , 120 , 121 ].…”
Section: Managing Antithrombotic Therapy In Thrombocytopenic Patiementioning
confidence: 99%
“…Of note, the vast majority of evidence pertains to short-term thrombocytopenia. We also identify additional factors associated with higher bleeding risk in this setting, including a history of bleeding, hematological malignancy and increasing bilirubin, creatinine, and prothrombin time [ 113 , 114 ]. An important concept guiding management decisions is that these patients have a high short-term risk of clinically significant bleeding, especially with full anticoagulation [ 22 , 24 , 102 , 113 , 123 , 124 , 125 ].…”
Section: Managing Antithrombotic Therapy In Thrombocytopenic Patiementioning
confidence: 99%